Drought tolerance of wheat and black oat crops at early stages of seedling growth - Steiner, Fábio (2019)
Seeds of wheat (Triticum aestivum L., cv. Jadeíte 11) and black oat (Avena strigosa Schreb., cv. Agro Planalto) were submitted to different osmotic potential levels induced by polyethylene glycol (PEG) with the objective of evaluate the effects of drought stress on seed germination and early seedling growth. Seeds were arranged in paper rolls and soaked in PEG solutions prepared with osmotic potentials form 0.0 (control), –0.2, –0.4, and –0.8 MPa and kept into a seed germinator, at 25°C for 15 days. A completely randomized design in a 2 × 4 factorial scheme with four replications of 50 seeds each was used. The results showed that by increasing of the osmotic potential level, germinated seeds number, germination rate index, root and shoot length, shoot and root dry matter, and seedling vigor index decreased, while mean germination time (MGT) and root:shoot ratio (RSR) increased in both crops. Additionally, black oat is more susceptible than wheat to drought stress, with germination response declining more rapidly with decreasing osmotic potential. Wheat crop tolerates water stress of up to –0.8 MPa, without reducing germination of the seeds; however, the growth of shoots and roots is drastically inhibited by the highly negative osmotic potential. The initial growth of black oat crop is progressively reduced with the rise of osmotic potential levels.